The diagnostic accuracy and clinical utility of pediatric renal tumor biopsy: Report of the UK experience in the SIOP UK WT 2001 trial. Issue 6 (13th February 2019) - Jackson, Thomas J.; Williams, Richard D.; Brok, Jesper; Chowdhury, Tanzina; Ronghe, Milind; Powis, Mark; Pritchard‐Jones, Kathy; Vujanić, Gordan M.; ,
Abstract: Introduction: The International Society of Paediatric Oncology (SIOP) protocols recommend preoperative chemotherapy appropriate for Wilms tumors (WTs) in children with renal tumors aged ≥6 months, reserving biopsy for "atypical" cases. The Children's Cancer and Leukaemia Group (CCLG) joined the SIOP‐WT‐2001 study but continued the national practice of biopsy at presentation. Method: Retrospective study of concordance between locally reported renal tumor biopsies and central pathology review nephrectomy diagnoses of children enrolled by CCLG centers in the SIOP‐WT‐2001 study. Results: Biopsy reports were available for 552/787 children with unilateral tumors. 36 of 552 (6.5%) were nondiagnostic: 2 normal tissue, 12 necrotic, 9 insufficient sample, and 13 indeterminate results (disproportionately non‐WTs). The sensitivity and specificity of biopsy to identify tumors that did not require SIOP empirical preoperative chemotherapy were 86.0% and 99.6%, respectively. 13 of 548 (2.4%) biopsy results were discordant with nephrectomy; non‐WTs other than renal cell carcinoma and clear cell sarcoma of the kidney (CCSK) were poorly recognized. In children aged 6‐119 months, 480 of 518 (91.6%) had WT or nephroblastomatosis. 5 of 518 (1%) had benign tumors, and only one diagnosed on biopsy. Biopsy results correctly changed clinical management in 25 of 518 (4.8%), including identifying 19 of 20 CCSKs, but would have led to overtreatment in 5 of 518 (1%) or undertreatment in 4 of 518 (0.8%). In children aged ≥10 years, biopsy correctly changed management in 5 of 19 (26%) cases with no discordance. Conclusion: Biopsy is less effective at identifying non‐WTs than WTs and rarely changes management in younger children. Biopsy should be reserved in SIOP protocols for children ≥10 years and in younger children with clinical or radiological features inconsistent with WT.